Evaluating the effects of permanent subcutaneous insulin infusion versus multiple daily insulin injections on glycated hemoglobin (HbA1C) levels in patients with type 2 diabetes: a systematic review and meta-analysis based on clinical trials - Abdollah Mohammadian Hafshejani; Soleiman Kheiri; Zahra Karimi (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2024)
Background. Diabetes is one of the most common chronic and metabolic diseases. This systematic review and meta-analysis study aimed to compare the effects of multiple daily insulin injections against permanent subcutaneous insulin injections on glycated hemoglobin (HbA1C) levels in type 2 diabetic patients. Methods. Studies that compared the impacts of multiple daily insulin injections against permanent subcutaneous insulin injections on HbA1C levels and were published until the end of 2022 in international databases were searched and retrieved (nine randomized clinical trial studies). The Chi-squared test and I2 were used to determine the presence and size of heterogeneity. Results. The results of the analysis demonstrated that compared to the group of multiple daily insulin injections, HbA1C was significantly reduced in the group of permanent subcutaneous insulin injections, so that the standardized mean difference was equal to -0.26 (95% confidence interval: -0.46– -0.06 P=0.025). According to the results of Egger’s (P=0.333) and Begg’s (P=0.667) tests, publication bias was not observed in this study. Conclusion. Based on the available evidence, permanent subcutaneous injection of insulin could be significantly successful in reducing and controlling the level of HbA1C because the patients in the permanent subcutaneous injection group had lower levels of HbA1C. Practical Implications. In patients with type 2 diabetes, insulin treatment with the permanent subcutaneous injection method can better control the level of HbA1C than the multiple daily injection method.